MEDIA SOSIAL SEBAGAI UPAYA PENCEGAH RADIKALISME - Derina Rahmat, Dofa Muhammad Aliza, Virda Altaria Putri (Jurnal Ilmu Komunikasi, 2019)
This study found that the social media platforms are taking essential part in the life of every individual and can develop into a weapon of mass persuasion. However, the impact of rapid change within social media networks has created a devastating effect on the mind and society's perspective. As a consequence of these rapid changes, society is not able to decide which information is to absorb or pass it away. In addition, every individual or certain group has a great chance to persuade thoughts and actions within the framework of specific interests such as extremist movement, politics, and so on. Social media and online networking are considered to be anonymity with no cost or low cost as a means of mass communication. This makes social media platforms is an effective option to disseminate a variety of views, including extreme views to anyone who has network connectivity with online. There are steps that have been taken to prevent the communication and information technology of cyber patrols to prevent the dissemination of radical contents. Blocking accounts that contains radical materials can be an alternative to be taken in order to limit the information of radical understanding. However, the government is expected to take an important role in debriefing the fundamental ideology of Pancasila through students organization or social communities.